2020
DOI: 10.1158/1078-0432.ccr-19-3624
|View full text |Cite|
|
Sign up to set email alerts
|

Immune Checkpoint Blockade in Combination with Stereotactic Body Radiotherapy in Patients with Metastatic Pancreatic Ductal Adenocarcinoma

Abstract: The effectiveness of immune checkpoint inhibitors (ICI) is limited in pancreatic ductal adenocarcinoma (PDAC). We conducted a phase I study to evaluate the safety of ICI with stereotactic body radiation therapy (SBRT) in patients with metastatic PDAC.Patients and Methods: Patients enrolled must have received at least one line of prior systemic chemotherapy for metastatic disease. Cohorts A1 and A2 received durvalumab every 2 weeks plus either 8 Gy in one fraction of SBRT on day 1 or 25 Gy in five fractions on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…We next evaluated immunophenotypes associated with E-TLS in PDAC tumors by quantifying immune infiltrates by IHC and analyzing transcriptomic signatures from RNA-seq data of whole tumor tissue from FFPE sections as previously described for this patient cohort. 43 As expected, tumors with E-TLS contained significantly more CD3 + and CD8 + T cells and CD20 + B cells per/mm 2 1 of tumor tissue compared to TLS − tumors ( Figure 2a-b ). Recent studies in other tumor types have shown that CD103 is a marker of tumor reactive, 44 terminally differentiated, 45 and/or tissue resident memory 46–48 CD8 + T cells that may associate with B cell recruitment in cancer.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We next evaluated immunophenotypes associated with E-TLS in PDAC tumors by quantifying immune infiltrates by IHC and analyzing transcriptomic signatures from RNA-seq data of whole tumor tissue from FFPE sections as previously described for this patient cohort. 43 As expected, tumors with E-TLS contained significantly more CD3 + and CD8 + T cells and CD20 + B cells per/mm 2 1 of tumor tissue compared to TLS − tumors ( Figure 2a-b ). Recent studies in other tumor types have shown that CD103 is a marker of tumor reactive, 44 terminally differentiated, 45 and/or tissue resident memory 46–48 CD8 + T cells that may associate with B cell recruitment in cancer.…”
Section: Resultssupporting
confidence: 78%
“…Single stained sections were digitally scanned using a Leica autoscanner at 20x magnification. Positive cells/mm 2 were analyzed using ScanScope software (Leica Biosystems), or Qupath. 23 Whole tissue regions (1 section/patient) were selected for analysis by identifying tumor cells surrounded by clear desmoplastic stroma in consultation with a pathologist (C.B.)…”
Section: Methodsmentioning
confidence: 99%
“…More and more clinical data show that cancer immunotherapy is a key step in clinical cancer treatment [19,20]. Cancer management methods, especially non-small cell lung cancer, melanoma, urothelial cancer, and kidney cancer, and some preclinical and clinical trials have confirmed that immunotherapy has achieved encouraging results in many malignancies, including pancreatic cancer [21][22][23]. However, based on available data, it is clear that ICB has limited success in pancreatic cancer, which is also related to the low immunogenicity and immunosuppressive tumor microenvironment of pancreatic cancer [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study only included three patients with metastatic PDAC, and their ORR to this strategy was not reported. Recently, a single-center phase I study tested SBRT plus durvalumab with or without tremelimumab as a second- or later-line therapy for metastatic PDAC patients [ 58 ]. Unexpectedly, the ORR for this strategy was only 5.1% [ 57 ].…”
Section: Current Status Of Immune Checkpoint Blockade Therapy For Pdacmentioning
confidence: 99%